Mediterranean marine heatwaves intensify in the presence of concurrent atmospheric heatwaves - Francisco Pastor; Laura Paredes-Fortuny; Samira Khodayar (Communications Earth & Environment, 2024)
Abstract Under climate change, temperature extremes have become more frequent and intense in recent decades, both in the atmosphere and in the ocean with devastating impacts on ecosystems and succeeding socioeconomic consequences. This is particularly true in climate change hotspots such as the Mediterranean region, where spatiotemporal compounding of extreme phenomena is becoming the norm. In the framework of a new spatiotemporal approach to heatwave detection, which tracks the evolution of the phenomena throughout their life cycle, the concurrence of marine and atmospheric heatwaves is investigated in this study. Concurrency of both phenomena in time and space shows a relevant impact on the intensity of the marine heatwaves, while no relevant changes are observed in atmospheric heat waves. Therefore, we demonstrate that intensification in extreme temperature events is accompanied by the added local intensification effect of marine heatwaves when concurring with atmospheric heatwaves, especially in recent years.